Genetics factors related with the inheritance in autogamous plant populations - Baldissera, Joana Neres da Cruz; Valentini, Giseli; Coan, Marlon Mathias Dacal; Guidolin, Altamir Frederico; Coimbra, Jefferson Luís Meirelles (Revista de Ciências Agroveterinárias, 2014)
The knowledge of the genetic control of a particular trait is essential for success in the breeding program, because then it is possible to direct the work and choose the best method of conducting the segregant population. In autogamous species genetic control can be studied using segregated populations. It is from them that the genetic parameters of importance can be estimated, such as the heritability, which reflects the proportion of phenotypic variance that can be inherited, the number of genes, that indicates the type of inheritance that the studied character composes, heterosis that is the superiority of a hybrid generation over the parental average. In addition to these parameters, it can be estimated the general combining ability, that assesses the average behavior of a parent in a series of hybrid combinations being associated with additive effects of alleles and the action of epistatic type additive, and specific combining ability, that considers the hybrid combinations that are higher or lower than the expected relative to average performance for their parents, emphasizing the importance of interactions resulting from nonadditive genetic complementation between the parents.